25 years of providing evidence on road safety interventions at the city level - Katherine Pérez; Katherine Pérez; Katherine Pérez; Elena Santamariña-Rubio; Maria José López; Maria José López; Maria José López; Maria José López; Lucia Artazcoz; Lucia Artazcoz; Lucia Artazcoz; Lucia Artazcoz; et al. (Frontiers in Public Health)
Road traffic injuries are a significant public health concern, ranking among the leading causes of mortality and disability-adjusted life years lost globally, especially among the young population. Traditionally, road safety has been approached predominantly from a healthcare standpoint, with limited interventions from a comprehensive public health perspective. In Barcelona, the Agència de Salut Pública (Public Health Agency) has been monitoring road traffic injuries and evaluating road safety interventions since the late 1990s. This paper explores how Barcelona has addressed road safety over more than two decades through a public health lens, emphasizing the evaluation of intervention effectiveness, highlighting key success factors, and addressing the challenges encountered. First, we describe the road traffic surveillance system, providing insights into the context of mobility and road safety interventions in the city since the late 1990s. Since then, 10 interventions have been evaluated, encompassing legislation policies (helmet law, motorcycle driving license, and the penalty points system) and infrastructure measures (speed radars, advanced stop lines for motorcycles, safe routes to school, 30 km/h zone, and red-light cameras), as well as a cost–benefit study of speed radars. Next, the paper quantifies the overall impact of road safety interventions by estimating the difference between the observed number of road traffic injuries and the expected number if no interventions had been implemented from January 2008 to December 2023, stratified by gender, injury severity, and mode of transport. Since 2008, injuries were prevented in more than 34,800 individuals, including approximately 1,000 severe injuries. Mode-specific analysis revealed that more than 4,700 pedestrians, 12,300 car users, and 3,200 moped users benefited from injury prevention measures, while the number of injuries among motorcyclists was 5,200 higher than expected. This article discusses key success factors, the pivotal role of public health in road safety, and outlines future challenges, providing valuable insights for cities aiming to adopt a comprehensive public health approach to address road safety concerns.